Analysis of numerical investigation on strength plate of airdrome outerco-veres from affect more heavy air-ship - Бєлятинський, А.А.; Талах, С.М. (Proceedings of National Aviation University, 2010)
Weight is of used for air-transport are increasing impetuously and consequently is necessary define more precisely solution on strength of airdrome strict outercoveres. In methodology is considering flan task of investigation of strength-deformation state of half-space for interaction with soil-mass.Put on task is deciding with help effective numerical method – method of finite element.Example is considering of influence on half-space of above-heavy air-transport air-ship Аn-225.Engineering solution is compared with numerical fragment of outercoveres with 12 plate dimension 7,5 x 7,5 m and numerical solution in flan put on task of investigation combination half-space.Drawing of shift and strength-moment on result solution task are constructed. Analysis of numerical results of strength-deformation state plate outercoveres of airdrome are presented about agreement putting results on bending moment for space and flat put on task shat coincidences of result solution task in different putting of task are permitting to make conclusion about authentic of obtaining numerical solution.